Doing business in Jamaica (Price Waterhouse Centre for Transnational Taxation KingstonJA, 1985)
Discusses business conditions in Jamaica. Gives information about various aspects of Jamaican business life including exchange controls, regulatory agencies, investment incentives, banking and local finance, business entities, labour relations and social security, and exporting to Jamaica. Outlines audit requirements and practices, and accounting principles and practices. Discusses taxation at length.
IDS